Sentiment Analysis of Review Data of a Product Using Python - Santhi Priya, P; Venkateswara Rao, T (International Journal of Engineering and Technology, 2018)
The other name of sentiment analysis is the opinion mining. Itâ€™s one of the primary objectives in a Natural Language Processing(NLP). Opinion mining is having a lot of audience lately. In our research we have taken up a prime problem of opinion mining which is theSentiment Polarity Categorization(SPC) that is very influential. We proposed a methodology for the SPC with explanations to the minute level. Apart from theories computations are made on both review standard and sentence standard categorization with benefitting outcomes. Also, the data that is represented here is from the product reviews given on the shopping site called Amazon.Â Â